Code-Mixing and Its Impact on Followers’ Purchase Intention in Somethinc’s Instagram Captions - Wahyuningsih, Agung Tri (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2024)
This study investigates the practical use of English interpolated into Somethinc’s Instagram captions through code-mixing analysis. To do so, this research employs Muysken’s proposition to identify the English codes and their types. Further, this research also addresses followers to reveal their intention on the decision to buy or reject the products. Documenting the captions is purposefully done for collecting the data to present the English codes, and distributing questionnaire is intentionally conducted to seek the followers’ purchase intention. The result shows that among 20 captions taken from February 14th until April 26th 2024, there are 57 English codes found in three types of code-mixing comprising insertion with 35 data, alternation with 20 data, and congruent lexicalization with 2 data. Further, the fact shows that English use in Somethinc’s captions is very influential because 56,9% of the respondents decide to buy the products. This finding gives a new insight that the use of English words in promoting products will attract followers’ attention and intention to buy the products.